2013
DOI: 10.2528/pierc12083102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Ultra Wideband Diversity Techniques for on-Body Radio Communications

Abstract: Abstract-This paper presents an experimental investigations and analyses of ultra-wideband antenna diversity techniques and their effect on the on-body radio propagation channels. Various diversitycombining techniques are applied to highlight; how the overall system performance may be enhanced. Diversity gain is calculated for five different on-body channels and the impact of variation in the spacing between diversity branch antennas is discussed, with an emphasis on mutual coupling, correlation and power imba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…It has been investigated both in offbody [5][6][7] and in-body cases [8]. Perhaps the majority of the published papers are related to the various aspects of on-body situations [9][10][11][12]. For instance, in [7,[13][14][15] research related to UWB onbody radio channels are reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been investigated both in offbody [5][6][7] and in-body cases [8]. Perhaps the majority of the published papers are related to the various aspects of on-body situations [9][10][11][12]. For instance, in [7,[13][14][15] research related to UWB onbody radio channels are reported.…”
Section: Introductionmentioning
confidence: 99%
“…In [7][8][9][10][11][12][13][14], on-body radio channel characterisation was presented at the unlicensed frequency band of 2.45 GHz. UWB on-body radio propagation channel characterisation for body-centric wireless networks have been presented extensively in the open literature [15][16][17][18][19][20][21][22][23][24][25][26][27]. However, the sizes and shapes of the different human bodies will affect the propagation path and lead to different system performances.…”
Section: Introductionmentioning
confidence: 99%
“…From the measurement data it can also be concluded that at the higher frequencies the values of the mutual coupling are lower thanks to the better isolation between the antennas. For all antenna pairs, the mutual coupling remains below -15 dB over the investigated frequency band and, as stated in [18], mutual coupling below that value can be neglected. Therefore, our assumption that the mutual coupling between the antennas can be neglected is valid.…”
Section: ) Uwb Antennamentioning
confidence: 99%
“…Further on, in contrast to most of the research on UWB BANs, which apply pulsed signals and focus on on-body communication, e.g. [15], [17], [18], [20], etc., our focus is on off-body MB-OFDM UWB systems. The use of MB-OFDM technique allows lower power consumption and longer propagation distances [7].…”
Section: ) Uwb Antennamentioning
confidence: 99%
See 1 more Smart Citation